Therapeutic plasma exchange in patients in a portuguese ICU - Calça,Rita (2020)
Purpose: The aim of this study is to characterize a Portuguese Intensive Care Unit experience in therapeutic plasma exchange in critically ill patients. Methods: We performed a retrospective analysis of the patients treated with therapeutic plasma exchange between 2000 and 2019. Data on patient characteristics, therapeutic plasma exchange prescription, adjuvant therapy used, adverse events and outcome under treatment were collected. Results: A total of 101 therapeutic plasma exchange procedures in 20 patients were studied. Mean number of therapeutic plasma exchange sessions per patient was 5.1±1.3. The most frequent indications to begin this treatment were myasthenia gravis (25.0%) and anti-neutrophil-cytoplasmic antibody-associated vasculitis (15.0%). There were 45.5% adverse events and the most frequent was hypotension (15.2%). 98% of the complications were mild-to-moderate. The outcome was favorable in 60.0% of patients. Conclusion: Therapeutic plasma exchange is an effective and safe therapy in many diseases that had high morbidity and mortality prior to the use of this technique.